2016
DOI: 10.1039/c5cc09673a
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of a two-coordinate, acyclic diaminosilylene (ADASi): completion of the series of isolable diaminotetrylenes, :E(NR2)2(E = group 14 element)

Abstract: An extremely bulky boryl-amide ligand, [N(SiMe3){B(DAB)}](-) (TBoN; DAB = (DipNCH)2, Dip = C6H3Pr(i)2-2,6), has been utilised in the preparation of the first isolable, two-coordinate acyclic diaminosilylene (ADASi), viz. :Si(TBoN)2. This is shown to have a frontier orbital energy separation, and presumed level of reactivity, intermediate between those of the two classes of previously reported isolable two-coordinate, acyclic silylenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
91
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 48 publications
(18 reference statements)
3
91
0
1
Order By: Relevance
“…To access germanium(I) compounds bearing amide ligands, monomeric amido-germanium(II) halide precursor complexes 4-6 (Scheme 1) were prepared in good yields by standard salt metathesis reactions. The X-ray crystal structures of the new complexes 5 and 6 (see Supporting Information) revealed them to be monomeric and to have very similar structures to the previously reported complex 4 [18] and other closely related amido-germanium chloride systems, for example, L † GeCl. [11] Comparable to the syntheseso f1 and 2,t oluenes olutionso f compounds 4-6 were reduced with 0.5 equivalents of the magnesium(I) dimer {( Mes Nacnac)Mg} 2 ( Mes Nacnac = [(MesNC- Scheme1.Synthesis of compounds 7-9.…”
Section: Results and Discussion Ligandssupporting
confidence: 66%
See 3 more Smart Citations
“…To access germanium(I) compounds bearing amide ligands, monomeric amido-germanium(II) halide precursor complexes 4-6 (Scheme 1) were prepared in good yields by standard salt metathesis reactions. The X-ray crystal structures of the new complexes 5 and 6 (see Supporting Information) revealed them to be monomeric and to have very similar structures to the previously reported complex 4 [18] and other closely related amido-germanium chloride systems, for example, L † GeCl. [11] Comparable to the syntheseso f1 and 2,t oluenes olutionso f compounds 4-6 were reduced with 0.5 equivalents of the magnesium(I) dimer {( Mes Nacnac)Mg} 2 ( Mes Nacnac = [(MesNC- Scheme1.Synthesis of compounds 7-9.…”
Section: Results and Discussion Ligandssupporting
confidence: 66%
“…The three amide ligands chosen fort his study are depicted in Figure2.T he two boryl/silyl amides ( TBo L [18] and PhBo L [19] )h ave been previously reportedb yu s. Althougha tf irst glance they possess somewhat similar steric bulk to the amide ligands in the ditetrelynes, 1-3,t hey have the potential to act as weaker N p-donors towards coordinated tetrel centers, considering the possibility of competing N!B p-donation within the ligand itself. The third ligand used in the currentw ork is the alkyl/aryl amide, DBu L, [20] whichi sc onsiderably less bulky than the amides utilized in 1-3.H owever,g iven the smaller covalent radius of C versus Si, it should provide more steric protection to coordinated tetrel centers than that given by the well-established amide, -N(SiMe 3 )(Dip), which has been widely used for the kinetic stabilization of low-valent Group 14 compounds andclusters.…”
Section: Results and Discussion Ligandsmentioning
confidence: 99%
See 2 more Smart Citations
“…[4] However,c ompared to the very large family of stable carbenes,t he structural diversity of stable silylenes is still limited, [5] and most of known stable cyclic and acyclicsilylenes are only symmetrically substituted (A-F). [6][7][8][9][10] Only af ew exceptions with an unsymmetrical pattern have recently been reported, namely the acyclica mino(silyl) and amino(boryl) silylenes (G [11] and H [12] ), which are stabilized by p-a nd s-donating substituents.B oth compounds clearly show an ambiphilic reactivity that allows the activation of small molecules such as H 2 .T ot he best of our knowledge, as table silylene featuring two different p-donating groups remains elusive.Out of all the possibilities,wewere interested in an amino/ylide substitution pattern for the stabilization of heterocyclic silylenes (I). In contrast to amino substituents, which behave not only as excellent p donors but also as strong s acceptors toward the silylene center, an effect that is directly related to the electronegativity difference between nitrogen and silicon (3.0 vs.1.9), less-electronegative carbonbased p-donating substituents such as ap hosphonium ylides are strong p donors and poorer s acceptors.T herefore,w e assumed that the combination of these two types of substituents should enhance the nucleophilic character of the corresponding silylenes.Indeed, Driess et al reported that the symmetrical bis-ylide-stabilized silylene D shows an extraordinarily basic character and reacts even with ethereal solvents such as THF or DME.…”
mentioning
confidence: 99%